Trading and anchoring next to the African Pillars of Hercules. Late Punic and Italic amphorae from underwater sites around Ceuta (Spain) - Blanco Arcos, Francisco J.; López Jurado, Mª Reyes; Sáez Romero, Antonio M. (Rei Cretariae Romanae Fautorum Acta, 2023)
Since the 1970s, numerous ancient amphorae have been recovered from the deep sea in Ceuta, especially for the work carried out by Juan Bravo. Almost 50 years after these findings, the re-study of these late Roman-Republican transport containers found at different sites around the Bay of Ceuta has made it possible to update their typology and compare them with the cargo of other shipwrecks located in the western Mediterranean. This new study clarifies the role and relationships of the Ceuta coastline in the Roman Republican period in the context of the Strait of Gibraltar and adds another indicator to the study of maritime trade routes in the central-western Mediterranean and the distribution of certain groups of containers (T-7.4.3.0, Dressel 1, Lamb. 2) in land areas on the north-eastern side of the future Mauretania Tingitana.